Analisis Penerapan Metode Pembelajaran Kreatif dalam Meningkatkan Keaktifan Siswa di Sekolah Dasar Negeri 2 Selabaya - Iren Putri Salsabila; Muh. Hanif (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study explores how creative classrooms at SD Negeri 2 Selabaya can spark enthusiasm and participation among elementary school students. Through a qualitative case-study method, data were obtained from classroom observations, interview sessions, and supporting documentation. The findings show that activities like educational games, imaginative art projects, and lively group discussions help create an inspiring learning atmosphere where students feel encouraged to express themselves actively. Still, the success of these creative classes depends greatly on creative resources, including learning tools and environmental encouragement. Differences in facilities leave some students quiet and less involved, while those with stronger support tend to stand out. Ultimately, the creative classroom becomes both a stage for self-expression and a reflection of educational inequality, highlighting the need for schools to provide simple yet fair facilities for all learners.